Predictors and impact of early cerebral infarction after aneurysmal subarachnoid hemorrhage. (24th February 2015) - Jabbarli, R.; Reinhard, M.; Niesen, W.‐D.; Roelz, R.; Shah, M.; Kaier, K.; Hippchen, B.; Taschner, C.; Van Velthoven, V.
<x xml:space="preserve">Abstract</x> Background and purpose Cerebral infarction is a frequent and serious complication of aneurysmal subarachnoid hemorrhage (SAH). This study aimed to identify independent predictors of the timing of cerebral infarction and clarify its impact on disease course and patients' outcome. Methods All consecutive patients with SAH admitted to our institution from January 2005 to December 2012 were analyzed. Serial computed tomography (CT) scans were evaluated for cerebral infarctions. Demographic, clinical, laboratory and radiological data of patients during hospitalization as well as clinical follow‐ups 6 months after SAH were recorded. Results Of the 632 analyzed patients, 320 (51%) developed cerebral infarction on CT scans. 136 patients (21.5%) with early cerebral infarction (occurring within 3 days after SAH) had a significantly higher risk of unfavorable outcome than patients with late infarction [odds ratio (OR) 2.94; P = 0.008], a higher in‐hospital mortality (OR 3.14; P = 0.0002) and poorer clinical outcome after 6 months (OR 0.54; P < 0.0001). The rates of decompressive craniectomy (OR 1.96, P = 0.0265), tracheostomy (OR 1.87, P = 0.0446), the duration of intensive care unit stay and mechanical ventilation were significantly higher in patients with early infarction. In multivariate analysis, Hunt and Hess grades 4 and 5 (OR 2.06, P = 0.008), Fisher grades 3 and 4 (OR 3.99, P = 0.014), sustained elevations of intracranial pressure >20 mmHg (OR 5.95, P < 0.0001) and early vasospasm on diagnostic angiograms (OR 3.01, P = 0.008) were predictors of early cerebral infarction. Conclusion Early cerebral infarction after SAH is associated with severe clinical course and unfavorable outcome and can be reliably predicted by poor initial clinical condition, thick subarachnoid clot, early angiographic vasospasm and sustained elevations of intracranial pressure.